DEVELOPMENT OF NEUTRON INTERROGATION TECHNIQUES TO DETECT DANGEROUS SUBSTANCES - Natalia M. B. D´Amico; Roberto E. Mayer (European Scientific Journal, ESJ, 2015)
The transboundary movement of dangerous substances is being internationally regulated because of the environmental consequences caused by the incorrect management of these chemicals. The international community is committed with a multitude of agreements to control and detect the illicit traffic of such substances in port containers using nonintrusive techniques. Basel and Rotterdam Agreements, Programme 21 are some of the international agreements signed. After initial trials with an accelerator based neutron source, this work reports the following effort to build a reliable experimental data set of the gamma emissions that can, in practise, be effectively recorded from the chemical substances of interest as: mercury, chlorine, cadmium and chromium. When gamma emissions of each chemical element are identified at laboratory scale, the technique will be carried one step forward to test realistic cargo arrangements. Neutron techniques are expected to be used as confirmation tools according as the results of the Coordinated Research Programme (CRP) of the International Atomic Energy Agency (Mayer a et al., 2009).